2019
DOI: 10.1039/c9ob00473d
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of unsaturated lipid chains by thioether-containing lipid chains in cationic amphiphiles: physicochemical consequences and application for gene delivery

Abstract: New thioether-containing amphiphiles were designed, characterized and applied for gene delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For that purpose, we constructed new lipid chains featuring one thioether function within a linear saturated hydrophobic chain. [41] We demonstrated that the presence of one thioether function did not modify the amphiphilic nature of the molecules but affected their physico-chemical properties (e. g. fluidity and molecular surface area); efficient gene carriers could thus be obtained depending on the position of the thioether function within the lipid chain. These results echo other studies showing that the incorporation of a thioether functional group affected the temperature of fusion of ionic liquids [42] or the temperature of transition (T m ) of bolaamphiphiles.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For that purpose, we constructed new lipid chains featuring one thioether function within a linear saturated hydrophobic chain. [41] We demonstrated that the presence of one thioether function did not modify the amphiphilic nature of the molecules but affected their physico-chemical properties (e. g. fluidity and molecular surface area); efficient gene carriers could thus be obtained depending on the position of the thioether function within the lipid chain. These results echo other studies showing that the incorporation of a thioether functional group affected the temperature of fusion of ionic liquids [42] or the temperature of transition (T m ) of bolaamphiphiles.…”
Section: Introductionmentioning
confidence: 91%
“…To reach these goals, the new cationic amphiphiles (compounds 4 ac; Figure 1) were systematically compared to compound BSV-S12 (which is an efficient vector for gene delivery and that features one thioether function per lipid chain) . [41] and the reference compounds BSV36 (incorporating oleyl lipid chains) and BSV101 (featuring stearyl lipid chains). It is worth noticing that all these compounds possess a closely related chemical structures; they all possess the same polar headgroup (trimethylammonium) and spacer (phosphoramidate) varying only according to the number and position of thioether functions within lipid chains of exactly the same length (incorporating 18 atoms in its backbone).…”
Section: Introductionmentioning
confidence: 99%
“…It was probably due to the existence of unsaturated bonds increased fluidity by preventing the tight accumulation of lipids. 44 In addition, a gradual decrease in fluidity could be seen with increasing alkyl chain length among the four cationic lipids containing saturated alkyl chains because short-chain lipids tended to separate in the bimolecular clusters or ''rafts'' form in the layer, resulting in an uneven distribution of lipids across the membrane. Although the fluidity of RLS1-4 was slightly different, these 1/P values were generally around 6.…”
Section: Membrane Fluiditymentioning
confidence: 99%
“…Cells were transfected using BSV163/DOPE-plasmids complexes as demonstrated elsewhere (Bouraoui et al, 2019;Le Corre et al, 2014). In short, cells were seeded in 96-wells or 24-wells culture plates and were transfected upon reaching 80% confluency by adding lipoplexes, formed by spontaneous self-assembly of BSV163/ DOPE and 0.25 or 1 μg DNA at different CRs 2-5, to each well.…”
Section: In Vitro Gene Transfectionmentioning
confidence: 99%